Spinal Tuberculosis and Cold Abscess without Known Primary Disease: Case Report and Review of the Literature. (13th December 2016) - Patel, Rima; Gannamani, Vedavyas; Shay, Emily; Alcid, David
Abstract : Extrapulmonary tuberculosis (TB) is uncommon but not rare. Bone and joint involvement constitute about 10% of extrapulmonary TB cases, with the spine being the most frequently affected site. Spinal TB patients typically present with back pain but other constitutional or pulmonary symptoms may be absent, rendering the diagnosis difficult. This case explores challenges in the diagnosis of spinal TB. We report a case of a 39-year-old woman presenting with vague back swelling for many years. Imaging revealed osteomyelitis of the spine but initial studies and cultures were negative for Mycobacterium tuberculosis . The diagnosis was confirmed weeks later when cultures demonstrated Mycobacterium tuberculosis . Considering the severe complications of untreated spinal TB including paraplegia and need for surgical intervention, high suspicion is critical in early diagnosis.